ANALISIS KEBENARAN BERDASARKAN COHERENCE THEORY PADA IMPLEMENTASI KURIKULUM MERDEKA SEKOLAH DASAR - Huswatun Aulia; Donna Boedi Maritasari; Lilik Kurniatussolihah; Siti Zahroh (LPPM Universitas Muhammadiyah Bulukumba, 2024)
The independent curriculum is currently a topic of discussion among learning units. Where educational units complain that the implementation process is difficult for educational units in Indonesia to carry out. This means that the Independent Curriculum is not required to be implemented by educational units, one of which is elementary school education. However, implementation is based on the capabilities and resource readiness of each school. This research was conducted using a descriptive qualitative method with a literature review type of research. Based on the results of the researcher's study, the research results show that there is coherence or consistency in the provisions made by the Ministry of Education and Culture, Research and Technology regarding the Implementation of the Independent Curriculum. Where, in the implementation which provides guidance to elementary school units for implementing the curriculum, basic education units have difficulty implementing it. So, at the same time there is a provision that the Independent Curriculum is not required to be implemented in each school. However, the implementation of the Independent Curriculum is carried out according to the readiness and capabilities of each school, in fact these provisions are coherent or consistent in the implementation process.